Sunitinib Enables a Clinical and Pathological Complete Remission of Metastatic Renal Cell Carcinoma (mRCC) - Bo Peng; Jin Gong (Urology Case Reports, 2017)
Renal cell carcinoma (RCC) is the most common renal cancer, and has a poor prognosis in individuals with metastases (mRCC). In this report, we describe a 48-year-old woman with unresectable multiple liver metastases and a colonic metastasis of RCC who was treated with sunitinib in combination with hepatic microwave ablation and obtained a clinical and pathological complete remission. We consider that sunitinib combined with microwave ablation can prevent unresectable hepatic metastases of RCC from evolving, and that sunitinib alone can achieve clinical and pathological remission in patients with colonic metastasis of RCC.